2012
DOI: 10.1007/s12032-012-0274-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating coagulation disorders in the use of bevacizumab for metastatic colorectal cancer by thrombelastography

Abstract: The aim of this study was to evaluate coagulation disorders in patients with metastatic colorectal cancer treated with bevacizumab by using rotation thrombelastogram (ROTEM(®)) and correlate ROTEM(®) parameters with routine coagulation tests. A total of 18 colorectal cancer patients who received bevacizumab combined with chemotherapy were included. There was no statistically significant difference between results of platelet count, prothrombin time (PT) and activated partial thromboplastin time (APTT), fibrino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Ustuner et al did not find any significant changes in D-dimer and fibrinogen levels after the FOLFIRI-bevacizumab treatment [5], but we found a nonsignificant reduction in D-dimer levels in women and a significant decrease after the 12th cycle in men. This result is interesting because it reveals that D-dimer has a prognostic value in patients with colorectal and lung cancers [10].…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Ustuner et al did not find any significant changes in D-dimer and fibrinogen levels after the FOLFIRI-bevacizumab treatment [5], but we found a nonsignificant reduction in D-dimer levels in women and a significant decrease after the 12th cycle in men. This result is interesting because it reveals that D-dimer has a prognostic value in patients with colorectal and lung cancers [10].…”
Section: Discussioncontrasting
confidence: 81%
“…According to these findings, we speculate that there have been some alterations in the coagulation systems in patients who received chemotherapy. In colorectal cancer, there is only one small study published by Ustuner et al They examined changes in coagulation parameters in 18 metastatic colorectal cancer patients and did not find any significant changes in platelet count, PT, and aPTT at baseline and in the subsequent chemotherapy cycles [5]; however, their study population was small and had no gender differentiation [5]. In our study, we found a shortened aPTT after the 8th cycle in men but not in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two small studies suggested that ROTEM could predict thromboembolic complications in colorectal and prostate cancer respectively and a third detected persisting hypercoagulability in patients undergoing resection for intra-abdominal malignancies [29][30][31]. However, additional studies showed no difference between patients with cancer and healthy controls, nor could ROTEM differentiate between patients with regard to site of primary or stage of disease [27][28][29][30][31]. A criticism of these studies is that they were carried out on relatively small populations, often with mixed malignancies or sampled at different stages of disease or treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Reference ranges as previously established in a multi centre study of healthy individuals. 29 On reviewing parameters of ROTEM in the six patients who developed VTEs over the 12 month follow-up period, it is noteworthy that five of these patients had at least one measure that was outside the normal range. Only one patient had what might be considered a normal profile for ROTEM, but he had values for ML (INTEM) and MCF (EXTEM) which were on the upper limit of normal and three others, MCF and alpha (INTEM) and alpha (EXTEM) close to the upper normal limit.…”
Section: Discussionmentioning
confidence: 99%